On state of the ichthyocene in Lake Leb- edinoye (Iturup Island) in connection with functioning of salmon hatcheries - O. V. Zelennikov; R. A. Semenov (Известия ТИНРО, 2023)
Fish species distribution in Lake Lebedinoye is considered. The samples were collected by fry seine along entire coast of the lake. Ten species of ﬁsh were sampled in the coastal zone; juveniles of chum salmon Oncorhynhus keta, amur stickleback Pungitius sinensis, and japanese dace Tribolodon hakonensis were rather abundant, other species were few in number. Japanese huchen Parahucho perryi were noted among the latter species: both juveniles of different age and an adult specimen of ≈ 2 kg weight were caught.